0096 Body mass index (bmi), chronic musculoskeletal pain and adverse employment outcomes in older workers: the health and employment after fifty (heaf) study. (21st August 2017) - D'Angelo, Stefania; Palmer, Keith; Walker-Bone, Karen; Harris, Clare; Coggon, David; Linaker, Cathy
Abstract : Introduction: The combination of an ageing population and an obesity epidemic has important health and economic implications, with growing numbers of older people remaining in work. Obesity is a risk factor for musculoskeletal disorders, which are often more common and severe at older ages and limit work capacity. As part of a longitudinal cohort study on the impact of health on employment in later life, we explored the relation between BMI, chronic musculoskeletal pain and employment outcomes. Methods: Some 8, 000 50–64 year-olds recruited from 24 English general practices completed a baseline postal questionnaire about work, home circumstances and measures of health. Logistic regression was used to explore associations between BMI and pain (lasting >1 month in the past year and interfering with everyday activity) and work outcomes (health-related job loss, prolonged sickness absence, cutting down at work), adjusting for educational background and mental health. Results: A total of 7585 participants were included, 861 of whom were not in work for a health reason. More than a quarter (26%) of participants reported chronic pain and almost a quarter were obese. Adverse work outcomes were only weakly associated with obesity on its own but strongly associated with the combination of chronic pain and obesity (OR range 3.9–6.8). Significant associations were also seen in the underweight group (BMI <18.5) (OR range 3.9–14.1). Conclusions: Prevention of chronic pain and obesity is important, but weight control is of particular importance in older workers with musculoskeletal problems, in terms of work capability and job retention.